Valine Pathway Is More Crucial than Phenyl Propanoid Pathway in Regulating Capsaicin Biosynthesis in Capsicum frutescens Mill. - Bellur Chayapathy Narasimha Prasad; Harishchandra Bhaskar Gururaj; Vinod Kumar; Parvatam Giridhar; Gokare Ashwathnarayana Ravishankar
Capsaicin, a pungency factor alkaloid of Capsicum fruits, is biosynthesized by enzymatic condensation of vanillylamine, a phenyl propanoid intermediate, and 8-methyl-nonenoic acid, a fatty acid derivative from the leucine/valine pathway by capsaicin synthase. Biotic elicitors, such as aqueous mycelial extracts of Rhizopus oligosporus and Aspergillus niger, and abiotic elicitors, such as salicylic acid and methyl jasmonate, were incorporated to cell-suspension cultures of Capsicum frutescens. The maximum elicitation of capsaicinoids to the extent of 6-folds was noticed when mycelial extracts of R. oligosporus were incorporated to cell-suspension cultures. The phenyl propanoid intermediates were elicited to the extent of 3-4-fold, whereas the levels of 8-methyl-nonanoic acid increased 6-fold in R. oligosporus mycelial-extract-treated cultures. The enzymatic assays of caffeic acid O-methyl transferases, keto acyl synthase, and capsaicin synthase were performed in elicited and nonelicited cell-suspension cultures. These enzymes were overexpressed in R. oligosporus mycelial-extracttreated suspension cultures, which was also confirmed by reverse transcriptase polymerase chain reaction studies. This is the first paper on the overexpression of 8-methyl-nonanoic acid leading to capsaicin biosynthesis using elicitors.
Keywords: CAPSAICIN SYNTHASE; CAPSAICIN; KETO ACYL SYNTHASE; 8-METHYL-NONANOIC ACID; RHIZOPUS OLIGOSPORUS; RT-PCR; ELICITATION